Demográfiai öregedés Csongrád megye határán - Szónokyné Ancsin, Gabriella (Közép-Európai Közlemények, 2008)
There were major global transformations in the entire world during the time of the 20th century, including a boom of information and the population as well. According to the latest demographic forecasts the 21st century will witness an aging of the population. This assumption seems to become true, as the demographic structure of the societies of the developed world experienced a major transformation at the turn of the 20th and 21st centuries, resulting in an acceleration of the aging of the population. For the next 50 years in Europe, we may project a prevalence of serious demographic problems, which will by all means affect the social and economic development of the countries of the continent. The first part of this paper discusses the theoretical questions of aging. Then a brief overview is given on the process of aging in Hungary considering the individual settlements. Finally, the settlements of Csongrád county are separately evaluated from this type of analytical point of view.